The making of human concepts - Mareschal, Denis; Quinn, Paul C.; Lea, S. E. G., 1946- (Oxford : Oxford University Press, 2010)
Human adults appear different from other animals in their ability to form abstract mental representations that go beyond perceptual similarity. This book brings together leading psychologists and neuroscientists to tackle the age-old puzzle of what might be unique about human concepts.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Developmental psychology; Cognition -- Physiological aspects